MAF protein mediates innate resistance to proteasome inhibition therapy in multiple myeloma - Qiang, Ya-Wei (Blood, 2016)
Multiple myeloma (MM) patients with the t(14;16) translocation have a poor prognosis, and unlike other molecular subgroups, their outcome has not improved with the introduction of bortezomib (Bzb). The mechanism underlying innate resistance of MM to Bzb is unknown. In the present study, we have investigated how MAF overexpression impacts resistance to proteasome inhibitor (PI) therapy (Bzb and carfilzomib). High levels of MAF protein were found in t(14;16) cell lines; cell lines from the t(4;14) subgroup had intermediate levels, whereas cell lines from the other subgroups had low levels. High expression of MAF protein in t(14;16) was associated with significantly higher PI half-maximum inhibitory concentration values compared with other molecular subgroups. PI exposure abrogated glycogen synthase kinase 3β (GSK3β)-mediated degradation of MAF protein, resulting in increased MAF protein stability and PI resistance. Subsequent studies using loss-of-function and gain-of-function models showed that silencing MAF led to increased sensitivity to PIs, enhanced apoptosis, and activation of caspase-3, -7, -8, -9, poly (ADP-ribose) polymerase, and lamin A/C. In contrast, overexpression of MAF resulted in increased resistance to PIs and reduced apoptosis. These results define the role of MAF and GSK3 in the resistance of t(14;16) MM to PIs and identifies a novel mechanism by which MAF protein levels are regulated by PIs, which in turn confers resistance to PIs.